Low coverage of influenza vaccination among Chinese children aged 12-23 months: Prevalence and associated factors. - Joseph T F Lau; Catalina S M Ng; Anise M S Wu; Yee Ling Ma; Mason M C Lau (PLoS ONE, 2018)
This study aimed to investigate prevalence and associated factors of influenza vaccination (IV) among children aged 12-23 months. Our cross-sectional survey interviewed 489 parents of children aged 12-23 months anonymously at twelve maternal and child health centers in Hong Kong. Results showed that only 11.5% of the children had ever received IV (64.3% being subsidized). Adjusted for the child's age, significant factors of the children's IV included parental knowledge about governmental policy/recommendation (Adjusted odds ratio [AOR] = 2.64, 95%CI = 1.09,6.40), knowledge about annual IV requirement (AOR = 2.30, 95%CI = 1.21,4.38), perceived safety-related barrier (AOR≥0.14, 95%CI = 0.06,0.33), cue to action (AOR = 7.79, 95%CI = 3.45,17.58), and subjective norm (AOR = 4.59, 95%CI = 2.34,9.00). IV prevalence of children aged 12-23 months remained low despite a subsidization scheme. The higher IV prevalence of older children reported by other studies suggested that parents postponed action. Promotion campaigns should shift emphases from cost reduction and mass media approaches to dissemination of knowledge about IV policy and safety, enhancement of health professionals' advice, and creation of supportive subjective norm.